Evaluasi profil sensori produk sate Rembiga menggunakan metode flash profile dan rate-all-that-apply (RATA) [Sensory profile evaluation of Rembiga satay using flash profile and rate all that apply (RATA) method] - Arzani, Lalu Danu Prima; Putri, Destiana Adinda; Salsabilah, Aziza; Ulpiana, Mia (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2024)
Rembiga satay is an indigenous processed beef product from West Nusa Tenggara. It undergoes marination with distinctive spices before grilling, contributing to its unique flavor profile. The product's specialty lies in its sensory attributes, distinctly reflecting the characteristic traits of the Lombok region, making it irreplaceable by comparable products from other regions. This study's objective was to thoroughly examine the sensory profile attributes of Rembiga satay using Quantitative Descriptive Analysis. Two methods, namely Rate All That Apply and Flash Profile, were employed for this evaluation. The research involved the engagement of 100 consumer panelists assigned to evaluate the sensory characteristics of four different Rembiga satay products, considering aspects such as taste, aroma, flavor, and texture. Results from the Flash Profile and Rate All That Apply methods consistently indicated that panelists discerned analogous sensory attributes in Rembiga satay. Specifically, Rembiga satay Ririn showed a sensory profile characterized by grilled meat flavor, Rembiga satay Lomboku featured grilled meat flavor, grilled meat aroma, and smoky aroma, and Rembiga satay Napisah presented attributes such as fibrous texture, sweetness, juiciness, spicy aroma, and meat flavor. Meanwhile, Rembiga satay Sinasih exhibited a sensory profile inclusive of umami, chili spiciness, black pepper spiciness, smoky flavor, grilled meat aroma, and chewiness